Namūdzaju al-Ikhtibārāti al-Qowāidi Li al-Lughoti al-‘Arabiyyati Muassasan ‘alā an-Nazhōriyyati ACTFL - Mahmudi, Ihwan; Widyanti, Lina Nur; Jariah, Ainun; Rini, Fitri Setyo; Nisa, Salma Sholochatun (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2025)
Abstract This study aims to develop a arabic grammar test model based on the American Council on the Teaching of Foreign Languages (ACTFL) theory. ACTFL theory emphasises the importance of communicative skills in language learning, including grammar as a fundamental component in language ability. In this study, Arabic grammar test was designed to measure grammar competence in the context of authentic and communicative language use. The research method involved library research. The results show that the developed test model is in accordance with ACTFL standards, effective in evaluating Arabic grammar competence, and can be used as a valid and reliable measurement tool in Arabic language learning. This test model is expected to help educators in assessing students' grammar skills more comprehensively and accurately, as well as supporting the improvement of the quality of Arabic language learning at various levels of education.